Relationship Between Birth Weight and Stunting Incidence in Toddlers at Langara Health Center, Konawe Island : BBLR - Wahidah Rohmawati; Rida; Nur Hamsar Sarmin; Dian Rosmala Lestari; Abdul Sila; Bety Anisa Wulandari (Politeknik Karya Persada Muna, 2022)
Baground: The problem of stunting is important to solve, because it has the potential to interfere with the potential of human resources and is related to the level of health, even child mortality. Data from the world bank shows that the workforce who experienced stunting in infancy reached 54%. This means that as many as 54% of the current workforce are stunting survivors. The aim of this study to determine the relationship between of birth weight with stunting incidence in toddlers at Langara Health Center.Method: This research uses a cross sectional study design.Results: Based on the p value obtained through the Chi square test with a 2x2 table is 0.001. So that the p value < where (0.001) < (0.05) which means Ha is accepted, that is, there is a relationship between infant birth weight and the incidence of stunting in children under five in the working area of the Langara Health Center.Conclusion: Children born with a birth weight below 2500gr have a 9.625 times chance of experience stuting compared to children born with a normal birth weight.Keywords: Birth weight, stunting